Performance analysis of superconducting generator electromagnetic shielding. Issue 1 (November 2015) - Xia, D; Xia, Z
Abstract: In this paper, the shielding performance of electromagnetic shielding systems is analyzed using the finite element method. Considering the non-iron-core rotor structure of superconducting generators, it is proposed that the stator alternating magnetic field generated under different operating conditions could decompose into oscillating and rotating magnetic field, so that complex issues could be greatly simplified. A 1200KW superconducting generator was analyzed. The distribution of the oscillating magnetic field and the rotating magnetic field in rotor area, which are generated by stator winding currents, and the distribution of the eddy currents in electromagnetic shielding tube, which are induced by these stator winding magnetic fields, are calculated without electromagnetic shielding system and with three different structures of electromagnetic shielding system respectively. On the basis of the results of FEM, the shielding factor of the electromagnetic shielding systems is calculated and the shielding effect of the three different structures on the oscillating magnetic field and the rotating magnetic field is compared. The method and the results in this paper can provide reference for optimal design and loss calculation of superconducting generators.